Veno-venous extracorporeal membrane oxygenation using an innovative dual-lumen cannula following implantation of a total artificial heart. (January 2017) - Youdle, Jemma; Penn, Sarah; Maunz, Olaf; Simon, Andre
We report our first clinical use of the new Protek Duo TM cannula for peripheral veno-venous extra-corporeal life support (ECLS). A 53-year-old male patient underwent implantation of a total artificial heart (TAH) for biventricular failure. However, due to the development of post-operative respiratory dysfunction, the patient required ECLS for six days.